Superparamagnetic Composite of Magnetite-CTAB as an Efficient Adsorbent for Methyl Orange - Nor Harisah; Dwi Siswanta; Mudasir Mudasir; Suyanta Suyanta (Universitas Gadjah Mada, 2022)
In this study, a superparamagnetic composite of magnetite-cetyltrimethylammonium bromide (CTAB) has been prepared by the coprecipitation method and then applied as a charge-selective adsorbent of anionic methyl orange (MO). The VSM (Vibrating Sample Magnetometer) measurement suggests the superparamagnetic property of MNPs (Magnetite Nano Particles) with a magnetic saturation of 49.2 emu g–1. The SEM image exhibits the significant difference in particle size from nanometers in uncoated magnetite to micrometers in magnetite-CTAB. Calculations with ImageJ software indicate that the diameter of the composite is in the range of 2–13 µm, with an average diameter of 6.56 µm, possibly consisting of hundreds to thousands of magnetite-CTAB micelles. The adsorption kinetics of MO over magnetite-CTAB follows the pseudo-second-order adsorption model of Ho and McKay with a rate constant (k2) of 3.54 × 103 g mol–1 min. The adsorption isotherm is well described by the Langmuir model with a Langmuir constant (KL) of 7.46 × 104 L mol and a maximum capacity (qm) of 27.9 mg g–1. The developed material is intriguing because it can be easily and quickly recovered using an external magnet after adsorption and selectively adsorbs anionic dyes.